EFEKTIVITAS SENAM RIA ANAK INDONESIA UNTUK MENGENALKAN KONSEP ARAH BAGI ANAK LOW VISION - M. Miko Saputra (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract: Based on observations made, there is a low vision children with strabismus who experience mobility problems caused by a lack of understanding of the concept of direction. With the goal of helping to introduce the concept of direction for children with low vision in SLB Al-Hidayah Maek, researchers will assess the effectiveness of the Children's Gymnastics Ria Indonesia to Introduce Concept Direction for Children in Low Vision X SLB Al-Hidayah Maek.